أبعاد جودة الخدمات المصرفية الالكترونية وأثرها على رضا الزبائن ((دراسة ميدانية على عينة من زبائن مصرف التجارة والتنمية في مدينة بنغازي)) (Economic studies journal, 2022)
The aim of this study is to identify the availability of the dimensions of the Quality of Electronic Banking Services in the Bank of Commerce and Development and whether these dimensions have an impact on customers satisfaction through its indicators, which are Responsiveness, Reliability, Assurance, Empathy, Tangibility on the customers satisfaction in Bank of Commerce and Development in Benghazi. In this study, the descriptive analytical method was used to collect data in the applied study and analyze it using the Statistical Package for Social Sciences (SPSS) program. The study population is the customers of the bank under study, and the sample size was 97 customers. The results of the study showed the approval of all customers on the availability of quality dimensions of Electronic Banking Services as well as customer satisfaction with the quality of services provided to them. The study concluded that the best dimension in terms of quality is the dimension of Empathy, followed by the dimension of Responsiveness, then Tangibility, followed by the dimension of Assurance, and the least of the quality dimensions is the dimension of Reliability. All the dimensions of the quality of the Electronic Banking Service under study were high. The study came up with a set of recommendations, the most important of which is spreading the culture of applying Electronic Banking Services among customers through advertising. It is important for the bank's management to spread the awareness of the importance of E-marketing among bank's customers and employees.References• Gazi, M. A. I., Rahaman, M. A., Hossain, G., Ali, M. J., & Mamoon, Z. (2021). "An empirical study of determinants of customer satisfaction of banking sector: Evidence from Bangladesh", The Journal of Asian Finance, Economics and Business, 8(2), 497-503.• Khafafa, A. J.; and Shafii, Z., (2013), "Measuring the Perceived Service Quality and Customer Satisfaction in Islamic Bank Windows in Libya Based on Structural Equation Modelling (SEM)", Afro Eurasian Studies, 2(1&2), 56-71.• Rahaman, M. A., Ali, M. J., Kejing, Z., Taru, R. D., & Mamoon, Z. R. (2020). "Investigating the effect of service quality on bank customers' satisfaction in Bangladesh". The Journal of Asian Finance, Economics and Business, 7(10), 823-829.
Keywords: Quality of E-Banking Services; Customers Satisfaction; Bank of Commerce and Development